EFEKTIVITAS PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN AKTIVITAS DAN MOTIVASI BELAJAR MAHASISWA PADA MATAKULIAH STATISTIKA - Ribka Kariani Br Sembiring (MES: Journal of Mathematics Education and Science, 2018)
Abstract. This study aims to find out what cooperative learning method is most effective in improving students’ activity and motivation in Statistics subject. This research is a Classroom Action Research (PTK). The subjects of this study are the 5th semester students of PGSD Study Program with total number 35 students. Instruments used consist of: (1) Observation sheet of learning implementation; (2) Observation sheet of students’ activity in learning with assessment on students’ oral activities, visual activities, listening activities, writing activities and emotional activities; (3) Observation sheets of group effectiveness with assessment on the efficiency aspects of problem solving and member participation; (4) Questionnaire of motivation to find out to which extent the learning can improve student's motivation which is seen from the students perception of their satisfaction in learning. The research results show that when PBM learning model is used in cycle 1 and Jigsaw learning model is used in cycle 2, Jigsaw is better than PBM learning model.Keywords: Problem-based learning model, Jigsaw Learning Model, activity and learning motivation.